"No, You're Playing the Race Card": Testing the Effects of Anti‐Black, Anti‐Latino, and Anti‐Immigrant Appeals in the Post‐Obama Era. Issue 2 (18th July 2019) - Reny, Tyler T.; Valenzuela, Ali A.; Collingwood, Loren
Abstract : Despite a sizable literature on racial priming, scholars have failed to account for the shifting nature of racial appeals. First, theories of racial priming have not yet been widely applied to increasingly common anti‐immigrant and anti‐Latino political appeals. Second, theories of racial priming have not adequately accounted for both an increasingly racialized political climate and increased tolerance for explicit anti‐minority appeals. In two survey experiments fielded both before Trump's rise and after his presidential victory, we find the Implicit‐Explicit (IE) model always fails for anti‐black appeals, sometimes fails for anti‐immigrant appeals, but consistently holds for anti‐Latino appeals. While we find the null effects of implicit versus explicit anti‐black and anti‐immigrant appeals are partly driven by tolerance for the explicit appeals, we also find evidence that white Americans are adept at recognizing the racial content of appeals featuring widely used, congruent issue‐group pairs. Our findings shed light on conditions under which the IE model does and does not hold in the current political era.